(Poli)geny na język. Prolegomena do lingwistyki genetycznej - Krysiak, Adrian (Investigationes Linguisticae, 2010)
The paper is intended as an introduction to the field of genetic linguistics. The author tries to answer the question of what it means for a language to be a Darwinian adaptation and gives a few examples of “language genes”. Some perspectives for further research have been indicated as well.